Influence of misfit stresses on the dielectric permeability of ferroelectric superlattices BaTiO3/BaZrO3 - Boris M. Darinskii (Taylor & Francis Group, 2021)
The mechanisms of increasing the dielectric response of the BaTiO3/BaZrO3 ferroelectric superlattices in comparison with the characteristics of the bulk materials of the lattice are discussed. It is assumed that changes in the dielectric response in superlattices are caused by mechanical stresses arising in layers of the superlattice due to the mismatch of the sizes of the unit cells that make up the lattice of single-crystal layers. These stresses lead to the formation of longitudinal polarization in the layers of barium titanate and to the related contribution of the transverse component of the dielectric tensor to the effective permeability of the superlattice in the direction normal to the plane of the layers. The misfit stresses cause the appearance of a ferroelectric phase transition in the barium zirconate the lattice layers with an increase in the dielectric constant of these layers in the direction normal to the plane of the lattice layers. Highlights: Mismatch stresses in ferroelectric superlattices